Tinjauan Sensory Branding dan Psikologi Desain Kedai Kopi Kekinian Terhadap Perilaku Konsumen: (Studi Kasus: Mojo Coffee) - Aryani, Dewi Isma (Program Studi Desain Interior Unikom, 2019)
ABSTRACT In the retail field, branding innovation is done by sensory branding supported by the application of appropriate design psychology. Sensory branding utilizes the human senses to provide visitors with emotional experiences that can be achieved through materials, color schemes, lighting, window displays, and product displays in stores. The sensory branding that will be studied is primarily related to the sense of sight and taste. Whereas in terms of design psychology, it will be assessed based on what the visitor feels and the social interactivity tendencies of the people in it. Therefore, through this research will be presented the findings of sensory branding and design psychology elements in Mojo Coffee as a case study, especially those relating to the image of the branding of shop interiors, design styles, interior elements, and visual merchandising. Keywords: cafe, design psychology, sensory branding